Starch Granule Size and Morphology as a Proxy for Water Regime Influence on Zea mays - Wilks, Stefania; Louderback, Lisbeth A.; Boomgarden, Shannon (Ethnobiology Letters, 2021)
A wealth of information on the patterns of human subsistence and plant domestication has been generated from studies on maize (Zea mays) starch granules. However, very little work has been conducted on how the size and morphology of those granules might change as a function of water stress during the growing season. In the arid Southwest, the role of irrigation in growing maize is an essential parameter in many foraging models. Our study seeks to determine if there are significant changes in the size and other morphological attributes of starch granules from maize planted at Range Creek Canyon under two different irrigation regimes ranging from little water (once every three weeks) to ample water (once a day). Our results provide data on the effects of irrigation on Z. mays starch granules and, therefore, have implications for identifying archaeological maize and possibly determining past water regimes at Range Creek Canyon.